1982
DOI: 10.1093/ije/11.3.212
|View full text |Cite
|
Sign up to set email alerts
|

Life Time Occupation, Smoking, Caffeine, Saccharine, Hair Dyes and Bladder Carcinogenesis

Abstract: A case-control study of bladder cancer in two northern counties of New Jersey was conducted to investigate a tumour that has been considered to be strongly associated with industrial and environmental exposures. The study population included 75 bladder cancer cases and 142 controls. Cases and controls were matched for race, sex, age, place of birth and place of residence. Statistically significant associations with bladder cancer and risk ratios of greater than 2.0 were found for cigarette smoking and for work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
2
2

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(28 citation statements)
references
References 0 publications
0
24
2
2
Order By: Relevance
“…In our study, the age-adjusted OR for all smokers vs. nonsmokers was assessed at about 4, i.e., higher than in studies conducted in Britain (Doll and Peto, 1976;Carwright et al, 1983;Morrison et al, 1984), and the USA (Hammond and Horn, 1958;Cole et al, 1971;Morrison et al, 1984;Najem et al, 1982;Hartge et al, 1987); it was a little lower than the risks reported in Italy (Vineis et al, 1984) and Argentina (Iscovich et al, 1987). Relative risks observed in Denmark, where black tobacco has been traditionally smoked, vary from 1.9 (Mommsen et al, 1983) to 3.6 (Moller-Jensen et al, 1983.…”
Section: Blackcontrasting
confidence: 60%
“…In our study, the age-adjusted OR for all smokers vs. nonsmokers was assessed at about 4, i.e., higher than in studies conducted in Britain (Doll and Peto, 1976;Carwright et al, 1983;Morrison et al, 1984), and the USA (Hammond and Horn, 1958;Cole et al, 1971;Morrison et al, 1984;Najem et al, 1982;Hartge et al, 1987); it was a little lower than the risks reported in Italy (Vineis et al, 1984) and Argentina (Iscovich et al, 1987). Relative risks observed in Denmark, where black tobacco has been traditionally smoked, vary from 1.9 (Mommsen et al, 1983) to 3.6 (Moller-Jensen et al, 1983.…”
Section: Blackcontrasting
confidence: 60%
“…Most previous studies reported either null associations 2,6,[17][18][19][20][21][22][23][24] or slightly positive associations 4,5,[25][26][27][28][29] between consumption of alcoholic beverages and risk of bladder cancer. Our results regarding beverage-specific consumption are in agreement with some, but not all, previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…All published case-referent studies reporting information on occupations and absolute numbers of cases and referents were taken into account. The following were subsequently excluded: (i).two papers giving information on a few chemical exposures but not on job titles or industrial acti,vities (24,26); (ii) those reporting data only for a very.limited list of occupations (less than 10) (3,7,9,16,18); (iii) 'those aiming at hypothesis generation, such as routine mortality statistics by oc- Populat ion-based study: cases randomly selected among all (491) incident cases occurring in 1967-1968 in 87 cities of the Boston area (20-89 years of age); referents a random sample of 20-to 89-year-old residents, matched for sex and year of birth ; 140/470 case and 781500 referent interviews obtained from spouse or next-of-kin (men and women); interview on the whole occupational history; control of confounding by age and smoking habits Population-based study: elig ible cases were all patients with newly diagnosed bladder cancer in three Canadian provinces (1974-1976)(77 % interviewed); referents matched for sex, age, and neighborhood (refusals were 20, 4, and 0 % in the three provinces; refusing referents were substituted); male cases had higher education and income than the referents; interview on the whole occupational history; control of confounding by age (matching) and smoking Mixed design: originally eligible cases were all those (N = 274) reported to the Finnish Cancer Registry in 1975-1976 for five Finnish provinces; postal questionnaires sent to 269 cases and 271 sex-and age-matched hospital referents or their relatives; responses were 80 % (cases) and 81 % (referents); the whole occupational history collected; control of confounding by age (matching)…”
Section: Selection Of the Studiesmentioning
confidence: 99%